Nihilism and the Consciousness of Revolt - Šerpytytė, Rita (Religija ir kultūra, 2011)
The article focuses on the question concerning the relationship between nihilism and rebellion consciousness. This aspect of the theory of nihilism is considered through the context, which seems “extraneous” or even opposite to the rebellion consciousness, i. e. by discussing the phenomenon of “nonresistance” or “surrender”. The Prologue of the book by Spanish author Santiago Alba Rico serves as a theoretical provocation. Rico’s “Nihilism and Capitalism” opens with a story about a catastrophic event which remained unrevealed – as if it didn’t happen. The latter disposition of Western spirit, according to Rico, functions as an approach diagnosing the Everyday Nihilism. The mentioned understanding of nihilism is juxtaposed with Camus’ “paradigmatic” consideration of rebellion consciousness. The article also deals with the question concerning the genetic link between the denial motion in nihilism and the analogous motion respectively found in rebellion consciousness. The impossibility to treat these two opposite consciousness – nihilistic and rebellious – as overcoming the Nihilism is disclosed. Both these intentions of consciousness are equivalent in respect of Cynics’ practical argument. And it is namely so-called “major event”, which cannot be left unrevealed, serves as a chance of “salvation” for Reality.